Współpraca Związku Młodzieży Polskiej z UB w realizacji planów „ofensywy ideologicznej” w środowiskach młodzieżowych w województwie lubelskim - Wołoszyn, Jacek (Pamięć i Sprawiedliwość, 2008)
The Association of the Polish Youth (Związek Młodzieży Polskiej, ZMP) established in July 1948 became one of the most important helpers of the party and state authorities when implementing the ‘ideological offensive’ among the young generation. The aim of the organization, among others, was to engage the youths in the ‘class fi ght’. That is why the ZMP (which from 1951 was the only official youth organization) supervised all forms of activities of the youth who where deprived of any possibility to gather outside structures subordinated to communists. Carrying out the tasks entrusted to them, the ZMP authorities co-operated with another institution which was equipped with means of ‘disciplining’ different social groups – the Offi ce of Security (Urząd Bezpieczeństwa, UB). The UB employees perceived the ZMP as both the ally in the process of supervising the youth and also the next ‘surveillance object’. That is why in the documents executed by them we may fi nd fragments referring to using the ZMP, and to be more exact, the leaders and members-confidents as a source of information on the moods of the youth. In some cases the ZMP members helped select candidates for secret collaborators. Sometimes the selected activists also pursued other goals: isolating the young generation from the ‘undesirable’ – according to the party and state authorities– infl uences of teachers, scout instructors, priests. The ZMP activists organized propaganda operations orchestrated by the UB consisting in condemning a catechist or a form tutor. Simultaneously, the officers recruited from the community secret collaborators whose task was to keep surveillance over all youths, including the members as well as the leaders of the ZMP. The described methods were typical of the daily work of security apparatus bodies co-operating with the ZMP as one of the creators of the Stalinist system responsible for the youth circles. The representatives of the UB similarly as the representatives of the communist party could treat the Association in a strictly utilitarian manner being interested only in using it for the realization of specific – sometimes short-term – goals. The co-operation between those organizations was to be secret and unknown to society. Lublin region serves as the example illustrating the cooperation between the ZMP and the UB among others on disciplining the youth.